Analisis Semantik-Stilistika Lirik Lagu Albi Ya Albi Karya Nancy Ajram: Representasi Konflik Batin dan Makna Konotatif - Renny Dwi Arumsari; Vira Hilma Fadhila; Mila Alinda Hastuti (Institut Agama Islam Negeri Metro, 2026)
This study examines the connotative meanings and stylistic devices found in the lyrics of Albi Ya Albi by Nancy Ajram using a semantic and stylistic approach. Arabic popular song lyrics function not only as musical elements but also as linguistic texts that convey emotional, psychological, and cultural meanings. This qualitative descriptive research employs text analysis as the primary method, with the song lyrics serving as the main data source. Data were collected through documentation and close reading techniques, followed by identification, classification, and interpretation of figurative language and connotative meanings. The findings indicate that the lyrics predominantly employ figurative language, particularly personification, metaphor, repetition, and rhetorical questions, to express emotional conflict and inner psychological struggle. Connotative meaning appears more dominant than denotative meaning, as linguistic expressions are used symbolically to represent emotional exhaustion, love-related trauma, and internal dialogue. The use of personification, especially the portrayal of the “heart” as an entity that can be addressed and questioned, highlights the separation between rational awareness and emotional experience. These findings demonstrate that semantic and stylistic analysis is effective in uncovering implicit meanings in Arabic popular song lyrics and contributes to a deeper understanding of contemporary Arabic linguistic expression. These findings indicate that contemporary Arabic song lyrics in colloquial varieties are valuable for examining semantic and stylistic developments in modern Arabic dialectology.